Reinforced concrete frame and brick masonry infill type composite construction for residential buildings up to four storeys founded on compressible soils - Singh P.K. (My University, 2025)
Residential buildings up to four storeys can be constructed with either load bearing brick masonry (BM) wall, moment resisting reinforced concrete (RC) frame having BM partition wall, or composite type comprising RC frame and infilled BM wall. Adopting a particular sequence of composite construction, RC frame and BM wall have good shear connection resulting in an integral structure. Considerable research has already taken place on infilled masonry and it has been well established that under racking, load stiffness and strength of the composite increase many times that of the enclosing frame. From the presented discussion on existing research publications, it is concluded that a four-storey residential composite building having required quality 230 mm thick brick masonry wall is safe in earthquake condition, in any part of the country. However, due to very stiff nature of the composite building, it is desirable that it is founded on compressible soil media. Comparing the three types of construction, it is inferred that the composite building is stiff, strong, economical, aesthetically better and speedy and easy in construction using the local material and skill, and more research in the area is needed for its mass application in the field.